KINERJA DINAS PARIWISATA BALI BERDASARKAN KONSEP VALUE FOR MONEY - Suryantari YS, Putu Dewi; Ulupui, I Gusti Ketut Agung (E-Jurnal Akuntansi; Vol 17 No 2 (2016), 2016)
The purpose of this study is to determine the performance of tourism in Bali in 2015. The data used in this research is the realization of the financial achievement of the Bali Tourism Office located on Government Agencies Performance Accountability Report (LAKIP) in 2015. Data collection methods used were documentation and interviews, Data analysis technique used is quantitative descriptive analysis. Based on the analysis on the entire program is implemented, namely the seven programs it is known that based on the analysis of the economic aspects, the entire program has been running economical with their budget savings in each program. Based on the analysis of aspects of the efficiency of the entire program is already running efficiently. Based on an analysis of the effectiveness of existing aspects of the program that runs less effective, namely in tourism destination development program.
Keywords: performance, value for money, economy, efficiency, effectiveness